Nurses’ knowledge, attitude, and practice of low-flow oxygen therapy and humidification - Tang, Naiwang; Li, Haiying; Zhang, Jiayi; Ling, Hua; Shi, Linlin; Zhang, Huili; Guo, Qi; Yu, Ronghuan (Frontiers in Medicine, 2024)
Objective: Nurses are key in administering oxygen therapy and managing its potential adverse effects in medical settings This study aimed to investigate the knowledge, attitudes, and practices (KAP) regarding low-flow oxygen therapy and humidification among nurses. Methods: This cross-sectional study was conducted from January 2024 to March 2024 at Shanghai Xuhui Central Hospital. Demographic data and KAP scores were collected through questionnaires. Result: A total of 243 valid questionnaires were collected. Among them, 228 (93.8%) were female, and 93 (38.3%) had been working for more than 10 years. The mean scores for knowledge, attitudes, and practices were 11.11±4.30 (Ranging 0-18), 29.14±3.41 (Ranging 7-35), and 28.07±4.73 (Ranging 7-35), respectively. Multivariate logistic regression confirmed that knowledge (OR = 1.302, 95% CI: [1.167-1.453], p < 0.001) and attitudes (OR = 1.196, 95% CI: [1.080-1.325], p < 0.001) were independently associated with proactive practices. Structural equation modeling (SEM) corroborated the direct influences of training (β = 3.210, p < 0.001) and clinical experience (β = 2.044, p = 0.002) on knowledge, with knowledge (β = 0.379, p < 0.001) and gender (β = -1.642, p = 0.037) directly impacting attitudes. Additionally, knowledge (β = 0.395, p < 0.001), attitudes (β = 0.340, p < 0.001), and equipment utilization (β = 1.098, p < 0.001) directly influenced practices. Conclusion: Nurses demonstrated inadequate knowledge, positive attitudes, and inactive practices towards low-flow oxygen therapy and humidification. Enhanced training and increased clinical experience are recommended to improve nurses' knowledge and practice in this area.